L14 DNA dataset. - Zimmermann, Heike Hildegard; Raschke, Elena; Epp, Laura Saskia; Stoof-Leichsenring, Kathleen Rosmarie; Schirrmeister, Lutz; Schwamborn, Georg; Herzschuh, Ulrike (PANGAEA, 2017)
has to submitted by author
Ancient DNA dataset, pollen and non-pollen palynomorphs of four permafrost cores hand-pieces, Bol'shoy Lyakhovsky Island
Keywords: AWI_PerDyn; Permafrost Research (Periglacial Dynamics) @ AWI